Determination Of Had Kifayah Zakat Among Pre-graduate Students At Universiti Sains Islam Malaysia (USIM) - Abdul Manan Ismail; Mushaddad Hasbullah; Mohamad Zaharuddin Zakaria; Mohd Nasir Abd Majid; Ahmad Zaki Salleh; Hussein 'Azeemi Abdullah Thaidi; Mohd Afiq Ab Jalil; Arieff Salleh Rosman; Aqeel Khan (Journal for Educators, Teachers and Trainers, 2024)
Had Kifayah refers to a minimum basic necessity rate set based on the current cost of living. The objective of this paper is to determine the current Had Kifayah for asnaf candidates focusing more on USIM Pre-Graduate students as the target group. The research method used are the qualitative and quantitative which apart from referring to existing writing and references, a survey was conducted to obtain the latest data from asnaf students through previous databases. The survey has been conducted via online instead one to one interview due to Covid-19 pandemic. Through a survey that covers aspects of student spending and income, the average of spending method has been used as per agreed with all team members to determine the Had Kifayah, in line with the method used by the state Islamic religious council as a reference. With the improvements made in the agreed calculation system, a more accurate calculation method has been developed and at the same time can help the process of proper distribution of zakat.